(untitled) (Modern education and development, 2025)
As climate change continues to impact weather patterns, ecosystems, and urban living conditions, architecture must evolve to meet these new challenges. Climate-responsive architecture refers to design strategies that adapt buildings to their local environmental conditions, reducing energy consumption while improving comfort and sustainability. This article explores the principles of climate-responsive architecture, innovative materials and technologies, and its critical role in shaping resilient, eco-friendly structures for the future.